Pengaruh Penerapan Good Corporate Governance terhadap Kinerja Keuangan Perbankan di Indonesia - Juliana Nasution; Maulana Abdul Malik Tambunan; Khofifah Shofy Aulia; Devara rustiana (Universitas Muhammadiyah Enrekang, 2022)
The application of the principles of Good Corporate Governance in general is very important to be applied in all companies, especially in the banking world. The purpose of this study is to find out about the influence of the implementation of Good Corporate Governance on the Financial Performance of Banking in Indonesia, which in this study uses a qualitative descriptive approach through a literature review. The purpose of good corporate governance is to consistently improve the company's development, values, performance, and contribute to maintaining the company's sustainability in the long term. Because it can have an impact on the expansion and development of banking companies, good corporate governance must be applied in the banking industry. The author concludes that Good Corporate Governance has a good influence on financial performance based on the evaluation of existing research.